Driving Green Business Practices through Environmental Awareness among MSMEs in Ibu Kota Nusantara (IKN) - Yudith Alexanderina Frans; Sarah Anistia; Finnah Fourqoniah; Poppy Alvianolita Sanistasya; Ummi Nadroh; Kayla Farya Arniandis (Research Synergy Foundation, 2026)
Environmental sustainability is a critical agenda for micro, small, and medium enterprises (MSMEs) supporting the development of Indonesia’s new capital, Ibu Kota Nusantara (IKN). This study examines the influence of environmental awareness on green business practices among MSMEs in the IKN region, including Samarinda, Balikpapan, Kutai Kartanegara, and Paser. Using a quantitative approach with data from 90 MSME actors, this research evaluates how cognitive environmental factors translate into sustainable operational behavior. The structural equation modeling (PLS-SEM) analysis reveals that environmental awareness has a positive and significant effect on green entrepreneurial intention (beta = 0.914; t = 14.536; p < 0.001), which in turn significantly drives green business behavior (beta = 0.835; t = 8.853; p < 0.001). The model demonstrates strong predictive power, with environmental awareness and intention explaining 83.6% and 69.7% of the variance in their respective target constructs. These results indicate that MSMEs with higher levels of environmental understanding are significantly more likely to implement eco-friendly production and managerial activities. These findings highlight the importance of internal cognitive factors in shaping sustainable business behavior. From a practical perspective, the results suggest that the IKN Authority and MSME support institutions should prioritize environmental literacy programs and targeted green business training. Strengthening environmental awareness is essential to ensuring local enterprises actively contribute to the long-term sustainability goals of the new capital. By fostering environmental consciousness, policymakers can effectively accelerate the transition toward a green economy among regional MSMEs.